1987
DOI: 10.1029/jc092ic12p13049
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale temperature variability: The influence of near‐inertial waves

Abstract: Measurements made with a towed thermistor chain and acoustic doppler current profiler in the seasonal thermocline of the Sargasso Sea are examined for relationships among small‐scale temperature “activity,” shear, and internal wave variability. Patches of intense activity measuring 5–10 m high and several kilometers in length are found to persist within a near‐inertial wave packet. The packet was tagged with a drogue and followed for about 16 hours as it was advected along an edge of a cold‐core ring. The patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Marmorino et al, 1987;Moum et al, 1992;Brandt et al, 1999). These thermistor strings had an accuracy of ∼10 −2 • C (Marmorino et al, 1987;Selschopp, 1997). As suggested from the "moored" observations by Thorpe (1987) and Hosegood et al (2004), such temperature variations can be expected even in deepocean environments, despite the local background buoyancy period, which is relatively large O(10-100 min).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Marmorino et al, 1987;Moum et al, 1992;Brandt et al, 1999). These thermistor strings had an accuracy of ∼10 −2 • C (Marmorino et al, 1987;Selschopp, 1997). As suggested from the "moored" observations by Thorpe (1987) and Hosegood et al (2004), such temperature variations can be expected even in deepocean environments, despite the local background buoyancy period, which is relatively large O(10-100 min).…”
Section: Introductionmentioning
confidence: 76%
“…whilst sampling at 0.1-4 Hz (e.g. Marmorino et al, 1987;Moum et al, 1992;Brandt et al, 1999). These thermistor strings had an accuracy of ∼10 −2 • C (Marmorino et al, 1987;Selschopp, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, this is impossible, but some progress has been made by the construction of high sampling-rate thermistors. 2,9,10 Initially, 1-Hz sampling-rate thermistors could only be used in a towed fashion cabled to a ship, 2 but modern electronics allow stand-alone sensors that can operate uninterruptedly for a period of a year. 10 When many are used, say 100 at 1 m intervals, time-depth images can be obtained that resolve internal waves and the larger, most energetic turbulence scales, provided the sensors' noise level and precision are sufficiently small (typically 0.001 • C or less).…”
Section: Introductionmentioning
confidence: 99%
“…It results in tens of meters high internal wave amplitudes and an ocean which is permanently in "wave motion." 2,3 Typical internal wave periods range from one day (at mid-latitudes) to one hour, in the deep ocean, and a few minutes, near the ocean surface. Typical (internal-wave-generated) turbulence scales vary from several tens of meters, the internal wave height and the buoyancy scale, to a few millimeters, the dissipation scale.…”
Section: Introductionmentioning
confidence: 99%
“…Toole et al, 1987). In the surface layers mixing is also associated with inertial motions that develop over the seasonal thermocline (Marmorino et al, 1987;Gregg et al, 1986), with the baroclinic upwelling jet (Kundu and Beardsley, 1991), or with the interaction of the two processes (Pelegrí and Richman, 1993). Pelegrí andCsanady (1991, 1994) found compelling evidence of intense diapycnal mixing within the Gulf Stream and suggested that it may be linked to mesoscale activity along its path.…”
Section: Introductionmentioning
confidence: 99%